(untitled) (Res Medica, 2014)
INTRODUCTION The accidental discovery of the Australia antigen (HAA) in 1963 by Blumberg and his coworkers is a classical example of biomedical serendipity. Its recognition not only stimulated a substantial amount of research into viral hepatitis, thereby adding considerably to our knowledge about this important disease, but has had far-reaching implications in the understanding of several other hepatic and systemic diseases. Indeed, its discovery may well be seen in the future to have been the all-important breakthrough in attempts at culture of the virus as a means of vaccine preparation for future prophylactic usage. THE DISCOVERY OF THE ANTIGEN Blumberg, a cytogeneticist working in the Philadelphia Institute for Cancer Research, was conducting a systematic study of the serum of patients who had received multiple blood transfusions. Using a technique of double diffusion in agar gel (Ouchterlony method) he searched for precipitating antibodies to inherited donor serum protein antigens, particularly those to low density betalipoproteins. A precipitating antibody was identified in the serum of a haemophiliac patient which reacted with an antigen which was quite dissimilar from lipoprotein antigens. This antigen was present in the serum of an Australian aborigine, and the term Australia antigen was coined (1, 2, 3,). This antigen is almost certainly identical to Prince’s SH antigen (4), and to avoid confusion the term hepatitis-associated antigen (HAA) is now considered by many to be more appropriate (5).